Instructional Digital Leadership for Strengthening Technology-Integrated Learning in Schools - Mulyati, Sri; Widiyan, Agung Purwa (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
The rapid advancement of digital technology has transformed teaching and learning processes, requiring school leaders to adopt instructional digital leadership that effectively supports technology-integrated learning. Although numerous studies have examined principals’ roles in educational digitalization, the existing evidence remains fragmented and has not been comprehensively synthesized from a technology-enhanced learning perspective. This study aims to synthesize current evidence on how instructional digital leadership strengthens technology-integrated learning in schools through a Systematic Literature Review (SLR). The review followed a structured literature selection process using Google Scholar, ScienceDirect, and Dimensions databases, covering publications from 2019 to 2025. Following predefined inclusion and exclusion criteria, 14 peer-reviewed articles were selected for qualitative synthesis. The findings reveal that instructional digital leadership contributes to technology-integrated learning through four interconnected dimensions: establishing strategic digital policies, strengthening teachers’ digital competence through continuous professional development, providing technology infrastructure and digital learning resources, and fostering a collaborative school culture that supports innovation and digital transformation. The synthesis further indicates that effective instructional digital leadership enhances teachers’ capacity to integrate digital technologies into pedagogical practices while promoting adaptive, student-centered, and technology-responsive learning environments. Nevertheless, persistent challenges including disparities in digital infrastructure, uneven teacher digital competence, and limited institutional support continue to influence implementation effectiveness. These findings highlight that instructional digital leadership is a critical enabling factor for sustainable technology-integrated learning and provide practical implications for school leaders, policymakers, and teacher professional development initiatives seeking to strengthen educational technology implementation in contemporary schools.